Assessment of Road Safety Through Geometric Design Analysis: The Case of Sagonsongan Diversion Road in Marawi City - Motalib, Jalaloden; Nasser, Nassib; Mangacop, Jamshed; Mamaingco, Abdul Warith (Journal of Interdisciplinary Perspectives, 2024)
This study critically assessed the impact of geometric design on road safety. This assessment was based on a detailed analysis of the case of Sagonsongan Diversion Road in Marawi City, the Philippines. Applying quantitative methods such as a survey using Real-Time Kinematics and software-based road designing using AutoCAD Civil 3D, the study thoroughly analyzed the geometric design elements of the road, such as horizontal alignment, vertical alignment, and superelevation. Thus, the study showed that all geometric features were highly inconsistent with the safety standards. In particular, the high curve radius and slope aspect ratio significantly increases the risk of traffic incidents. The evaluation of two key curve sections has demonstrated that the road's overall geometric design directly affects drivers' ability to keep their cars stable. To eliminate the risk of traffic wretchedness, this study has suggested several corrective measures, including redesigning the road to adjust the geometrical aspects to safe norms, setting accurately calculated speed limits, reinstalling road signs, and conducting continuous safety checks. These measures will help to bring the Sagonsongan Diversion Road’s design to the level of established safety standards and decrease possible incidents to the minimum. The study has provided important findings on the relevance of established road designing principles to road safety. This work can be useful for the existing discussion regarding engineering and policy measures that should be considered to enhance road safety, especially in countries with developing economies. This study has also illustrated the importance of continued geometric design assessment in ensuring road safety and adapting the safety requirements to the dynamic needs of road users.